O incidente de desconsideração da personalidade jurídica e sua aplicabilidade ao processo do trabalho - Oliveira, André Araújo de (2018)
Disregard of legal personality is provided for in our legal system, but until the recent amendment to the Code of Civil Procedure in 2015, without any form of application. Thus, it was up to the magistrate, through provocation of the party, to adopt the procedure he considered most appropriate. The legal forecast of the procedural incident removed the legal uncertainty that existed until then, so that the parties begin to know, in advance, the procedural track to discuss their incidence. In the Labor Procedural Law, there was already an indication of the application of the incident, via a subsidiary invocation of the general procedural rules, including the manifestation of the TST in this sense. Doubts were buried with the labor reform, brought by Law 13467/2017, which was clear in this regard. In order to understand the logic of the incident in this specialized, this thesis proposes the presentation of the principles of the work process, the scope of the civil process subsidiarity to the labor process, with the discussions around this theme, as well as the own institute of the disregard of personality and, of course, by the consequences of its non-observance by the Labor Judge, since even if labor reform had room for discussion, the legal amendment, as already mentioned, leaves no room for understanding other than its observance. It is also proposed to discuss the incident of disregard of the legal personality, invoking the principles that underpin its relevance, the general power of caution and the protection of urgency as a possible justification to avoid the need to install the incident, as well as the official impulse and possible resources to be handled in the reception or request for disregard of legal personality